Impact of Culturally Relevant Pedagogy on Black Learners Enrolled in Online Undergraduate Mathematics Classes - Lauren Hennings; Alexandra Schindel (Online Learning)
Scholars have often proposed the use of Culturally Relevant Pedagogy (CRP) as a way to improve the experience of Black learners in mathematics classrooms. Prior research shows Black learners show improvement in comprehension, engagement, motivation, and confidence as a result of CRP’s use. However, there is limited research on whether Black learners respond similarly when exposed to CRP in undergraduate remote learning environments. This qualitative teacher-researcher case study examines learners’ experiences in a remote undergraduate algebra course to explore CRP’s pedagogical design in a remote mathematics environment and its impact on three Black learners’ engagement, motivation, and confidence. Results show that as a result of the use of culturally relevant problems as part of the online course, specifically in weekly discussion boards and written reflection assignments, participants showed improved engagement, confidence, and motivation towards learning mathematics.